A study of MIPO by locking compression plate fixation in the management of distal tibial metaphyseal fractures - Venkateswarlu, Kurukunda; Madiga, Nagaraju; P, Sivababu (International Journal of Research in Medical Sciences, 2017)
Background: Management of distal tibial metaphyseal fractures has been a difficult area because of the subcutaneous position of tibia. Exposure of implant has been a major problem in open reduction and fixation of these fractures. Minimally Invasive Plate Osteosynthesis (MIPO) is an established technique for fixation of fractures of the distal third tibia. Our study is aimed at management of intra-articular and extra-articular fractures of the distal third tibia by minimally invasive plate osteosynthesis technique by locking compression plate and follow them prospectively. Clinical and radiological outcomes were studied and clinical indications & efficacy of the procedure reviewed. Methods: From June 2012 to May 2014, 22 patients of closed distal tibial metaphyseal fractures were operated by MIPO technique with a distal tibial locking compression plate having 4.5/5 proximal and 3.5/4 distal screw holes. The follow up duration was for 2 years at our hospital. Results: The mean fracture healing time was 5.5 months (range 4-13months). We had 90% of union rate with good ankle movements and walking distance in 75% of the patients. Pos-operatively we had complications of, superficial infection occurred in 2 patients, implant failure in 1 patient leading to non-union and delayed union in 1-patient each. Conclusion: MIPO technique provides good, stable fixation of distal tibial metaphyseal fractures. Although slightly delayed bone healing, MIPO decreases the incidence of non- union and need for bone grafting. This technique should be used in distal tibia fractures where locked nailing cannot be done like fractures with small distal metaphyseal fragments, vertical splits, markedly comminuted fractures and in fractures with intra-articular extension.